2015
DOI: 10.4049/jimmunol.1500709
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Stimulated Neutrophils Instruct NK Cells To Trigger Dendritic Cell Maturation and Promote Adaptive T Cell Responses

Abstract: Polymorphonuclear neutrophils (PMNs) are innate effector cells with pivotal roles in pathogen recognition, phagocytosis, and eradication. However, their role in the development of subsequent immune responses is incompletely understood. This study aimed to identify mechanisms of relevance to the cross talk between human neutrophils and NK cells and its potential role in promoting adaptive immunity. TLR-stimulated PMNs were found to release soluble mediators to attract and activate NK cells in vitro. PMN-conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 40 publications
1
51
1
Order By: Relevance
“…As previously shown, additional cell types, including macrophages and neutrophils, that are either resident in tissues or recruited to inflammatory sites, may interact each other and generate a cross talk with NK cells during the early phases of innate immune responses (16, 21, 22, 41, 58, 59). Thanks to the demonstration that eosinophils interact functionally with NK cells, the present study extends the number of innate cells participating in cross talks among cells of the innate immunity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As previously shown, additional cell types, including macrophages and neutrophils, that are either resident in tissues or recruited to inflammatory sites, may interact each other and generate a cross talk with NK cells during the early phases of innate immune responses (16, 21, 22, 41, 58, 59). Thanks to the demonstration that eosinophils interact functionally with NK cells, the present study extends the number of innate cells participating in cross talks among cells of the innate immunity.…”
Section: Discussionmentioning
confidence: 96%
“…β-actin and CD63 amplifications were performed for 30 cycles using the same conditions and served as internal controls; primers used were: β-actin up 5′ ACTCCATCATGAAGTGTGACG; β-actin dw 5′ CATACTCCTGCTTGCTGATCC; CD63 up 5′ CAGCCATGGCGGTGGAAG and CD63 dw 5′ CCACTCCCCCAGATGAGG. PCR products were run on a 0.8% agarose gel and visualized by ethidium bromide staining (16, 44). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NK cell depletion studies were used to show that DCs bridged the temporal relationship between NK and CD8 + T cells within the liver tumor microenvironment. Recent work by Riise et al (69) showing that TLR7-stimulated neutrophils instruct NK cells to stimulate DC maturation may be a potential mechanism for entolimod-mediated NK cell activation of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…in vivo models of bacterial infections revealed that neutrophil production of proinflammatory cytokines, such as IL‐12, IL‐15 and possibly IL‐18, is crucial to polarize the immune response and favours NK cell‐mediated IFNγ production . In agreement, in vitro experiments showed that human TLR‐stimulated neutrophils were involved in NK cell activation in an inflammasome‐dependent manner .…”
Section: Nk Cells and Neutrophilsmentioning
confidence: 68%